الصكوك الإسلامية ضوابطها ودورها في الاستثمار وتطبيقها في ماليزيا (هيئة الأوراق المالية نموذجا) - Issahaku Abdullah (Universiti Sains Islam Malaysia, 2024)
This study entitled “Sukuk (Islamic Bond): its regulations, its role in the investment and its applications in Malaysia, the Securities Commission in Malaysia as an example”. This study represents one of the modest attempts to link the study of the Sukuk with other transactions and how it is applied by the Securities Commission in the Malaysian model. The topic is choosing based on the following reasons: the intensifying debate and dispute over the Sukuk and how to deal with it and its legitimacy. Lack of interest of in-depth Sukuk study in Fiqh (Islamic jurisprudence) despite the importance of the Sukuk and its development, which is growing on daily basis. This study follows analytical and critical approach, as that will allow the researcher to address a wider range of the Sukuk in terms of linking securities with commercial and contemporary transactions, and it attempts to discuss its application and benefits in this modern era. The main objectives of this study are: a general survey of the rulings and provisions of the Sukuk, its regulations, its role in the investment and its applications in Malaysia. This subject formulates a set of sub-questions which are focused in the core of the problem under investigation. Among those sub-questions are: What is Sukuk? What are the Islamic regulations of the Sukuk? What is the role of Sukuk in Islamic investment? What is the success of the Malaysian Securities Commission in issuing Sukuk and its applications in dealing with securities? The findings of this study yield several conclusions, including: First, the different types of the Sukuk applied in Malaysia are Sharia-compliant. Second: the Sukuk became an important role player in the national economy of Malaysia, and it helped the development of productive and service projects. Third, The Sukuk has regulations which shall be observed in activating its role in investment, and which merit research and studies, in which the rulings of transactions renew daily, especially in this time. Fourth: The Sukuk and the various forms of its investments is the main source of revenue for the Islamic banking sector, as considered by the Sharia Accounting Organization and the Council of the securities and banking as a good alternative to the benefits of usury.